The brave new world of digital personal assistants: Benefits and challenges from an economic perspective - Oliver Budzinski; Victoriia Noskova; Xijie Zhang (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2018)
The paper applies economic theories to give an overview of the emerging phenomenon of digital personal assistants (DPAs). A DPA is an intelligent automated system that interacts with the user through a dialogue in natural language, and meanwhile applying third-party services to obtain information and perform various actions. We analyze the benefits of increasing usage of DPAs, such as reduction of transaction costs, enhanced organization efficiency, procompetitive effects, and boosting the e-commerce economy. Besides benefits, however, adopting DPA in life may also contain some risks and downsides, which may reduce the positive welfare effects or even lead to decreasing welfare: biased services, market power on the DPA market and economic dependence on a dominant DPA, potential leveraging of DPA suppliers' market power into neighboring markets, personalized data (ab)use and privacy, media bias and manipulation of public opinion.
Keywords: L86; L13; L40; D43; D90; D82; K21; O33; 330; digital personal assistant; DPA; platform economics; economics of privacy; imperfect competition; behavioral economics; antitrust; smart speaker; auto-mated assistant; virtual assistant; digital butler; digital helper; digital assistant; speech-based interface; agent-based assistant; algorithmic assistant; digitization; digital economy